Is Virtual Reality (VR) Becoming an Effective Application for the Market Opportunity in Health Care, Manufacturing, and Entertainment Industry? - Kim, Kay (European Scientific Journal, ESJ, 2016)
The purpose of this paper is to analyze how virtual reality technology has been blossoming and applying in the past few years to quickly become the next big new products development in high technology industry. Thanks to this technology being backed by major tech and manufacturing firms, such as Facebook, Ford, and Sony, it has shown much promise in impacting our lives by bringing something completely new to our experience of processing data. There are three sectors in particular where it benefits most; healthcare, manufacturing, and entertainment. The paper explains in detail how these areas are positively impacted and applied.